Wikifreak-out: The Legality of Prior Restraints on WikiLeaks' Publication of Government Documents - Kyle Lewis (Washington University Journal of Law & Policy, 2012)
There is no Supreme Court precedent on the constitutionality of criminalizing the publication of leaked classified information, as the SHIELD Act proposes to do, because the U.S. government has never prosecuted anyone for doing so. The closest precedent is New York Times v. United States (Pentagon Papers), where the Court held as unconstitutional the government's effort to enjoin the New York Times from publishing a leaked copy of a top-secret government study of the Vietnam War. Part I of this Note examines the history of WikiLeaks, the current condition of the media, and the history of Pentagon Papers. Part II discusses why WikiLeaks' publication is comparable to that of the New York Times in Pentagon Papers. Part III of this Note proposes that WikiLeaks must be afforded the same First Amendment protection as was the New York Times in Pentagon Papers.
Keywords: Espionage; Freedom of information; Freedom of speech; Government documents; Prior restraint; Espionage Act of 1917; United States